Analisis Media Pembelajaran Daring DI Era Pandemi Covid-19 Pada Kelas III SD Negeri 027 Samarinda Ulu - Ding, Jepri; Hermawati, Desi (SISTEMA: Jurnal Pendidikan, 2020)
This study aims to determine the analysis of online learning in period Pandemic covid-19 in class III C SD Negeri 027 Samarinda Ulu. This research was a type of qualitative research. The subjects were teachers of class III C, headmaster, students class III C, and parents of class III C. Then, the data collection techniques used were interviews and documentation. The instruments used were teacher interview sheets, headmaster interview sheets, student interview sheets, parents interview sheets, and documentation. Furthermore, all the data that had been collected were then analyzed using descriptive qualitative data analysis techniques. Based on the results of the study, it could be concluded that the online learning becomes effective learning for teachers and students during the learning process from home using handheld electronic media, even though there were many challenges that teachers, students, and parents had to face when participating in online learning through Whatsapp.